2020
DOI: 10.1002/fsn3.2094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of simulated transport vibration on the quality of shiitake mushroom (Lentinus edodes) during storage

Abstract: The quality and shelf life of mushrooms are critical to their commercial viability. In this study, the effects of simulated transport vibration on postharvest quality of shiitake mushrooms (Lentinus edodes) were assessed over 12 days of storage. Furthermore, the protective performance of foam cushion material used in packaging during simulated transport was evaluated. Changes in respiration rate, weight loss, browning index, firmness, and malondialdehyde content were measured following vibration treatment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The water holding capacity of mushrooms is closely related to the degree of cell wall damage (Liu et al, 2021). In addition, changes in microstructure also affects the hardness of mushrooms (Tao, Chen, & Jia, 2020), which was confirmed by the SEM and TEM results of this study. Our results showed that water loss and degradation of soluble protein and crude polysaccharides resulted in cell damage and mycelium collapse, which was consistent with the tendency for hardness to decline.…”
Section: Discussionsupporting
confidence: 80%
“…The water holding capacity of mushrooms is closely related to the degree of cell wall damage (Liu et al, 2021). In addition, changes in microstructure also affects the hardness of mushrooms (Tao, Chen, & Jia, 2020), which was confirmed by the SEM and TEM results of this study. Our results showed that water loss and degradation of soluble protein and crude polysaccharides resulted in cell damage and mycelium collapse, which was consistent with the tendency for hardness to decline.…”
Section: Discussionsupporting
confidence: 80%
“…Celik, et al [44] reported that the weight loss of apple fruit increased with the prolongation of storage time and fruit damage. Mir and Shahbazi [15] and Tao, et al [45] reported similar results. The results of this study showed that the 'Shine Muscat' grapes' weight loss was greater in the compression treatment groups compared to the control group.…”
Section: Discussionmentioning
confidence: 54%
“…In some food SC contexts, road conditions such as vibrations during transportation play an important role in quality and marketable condition wastage [ 27 , 28 ]. Cold chain logistics (or temperature control logistics) for modern food SCs has been using RFID sensors over the logistic network to carry out the purpose of timely control of the storage and food temperature throughout the logistics process [ 29 ].…”
Section: State Of Artmentioning
confidence: 99%